Preparation Method, Product and Application of pH-Responsive Sustained-Release Early Strength Agent
By forming a pH-responsive sustained-release premature strength agent for polyelectrolyte membranes on the surface of porous silicate minerals, the problem of slow development of cement stone compressive strength and shortening of cement slurry thickening time in deep-water cementing is solved, and early compression strength improvement and optimization of cement slurry thickening performance is achieved.
Patent Information
- Application Number
- CN202411232808.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2044-09-04
AI Technical Summary
In deep-water cementing operations, the alternating temperature field environment of low seabed and high bottom of the well lead to slow development of cement stone compressive strength, affecting the cementing quality, and may cause blowout accidents. At the same time, the one-time addition of early strength agent will shorten the thickening time of cement slurry and affect pumping.
The pH-responsive sustained release premature strength agent is adopted, and the preparation method includes pore expansion treatment of porous silicate minerals and coated on its surface by vacuum-vacuum operation and layer-by-layer self-assembly technology to form a polyelectrolyte membrane to control the release of premature strength agent.
This technology can improve the early compressive strength of cement stone in low temperature environments, avoid rapid thickening of cement slurry, ensure the pumpability of cement, and achieve slow release of premature strength agents in alkaline environments, improving cementing safety.
Smart Images

Figure CN119100639B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete and oil and gas field development cementing, and in particular to a preparation method, product and application of a pH-responsive slow-release early strength agent. Background Art
[0002] With the continuous development and depletion of shallow oil and gas resources, deep and ultra-deep layers have become important strategic territories for oil and gas. Cementing technology is an essential link and key technology in the process of oil and gas development. For deepwater cementing operations, the biggest challenge is the alternating temperature field environment of low seabed temperature and high well bottom temperature. The low temperature environment affects the hydration rate of oil well cement, resulting in slow development of cement stone compressive strength, prolonging construction time, and affecting cementing quality, making it easy for formation oil, gas, water and other fluids to invade the wellbore and cause blowout accidents. It seriously affects the exploitation of oil resources in deepwater areas. However, when the wellbore depth reaches a certain level and a high temperature environment appears at the bottom of the well, the cement slurry is prone to rapid setting, affecting the rheology and workability of the cement slurry.
[0003] Early strength agent is an admixture that accelerates the early strength development of cement. It can promote the hydration and hardening of cement, thereby improving the early strength of cement. According to the chemical composition, early strength agent can be divided into inorganic, organic and composite types. Among them, inorganic early strength agent is used in larger amounts, including halides, sulfates, nitrates, silicates and carbonates. Among them, sodium sulfate can react with the hydration product CH, on the one hand, consuming liquid CH and generating caustic soda, which can accelerate the formation of AFt and C 3 S hydration; on the other hand, the extremely fine CaSO 4 The particles improve the 3 The reaction rate of S can be increased, thereby improving the early strength of cement paste. Introducing early strength agents into cement can indeed improve the early strength development of cement in low temperature environments, but as the well depth increases and the bottom temperature increases, cement slurry is prone to rapid setting, increasing cracks and pores in cement-based materials. Secondly, adding early strength agents at one time will shorten the thickening time of cement slurry, affect the pumpability of cement slurry, and cause a large conflict with the retarder. Summary of the invention
[0004] Based on the above content, the present invention provides a preparation method, product and application of a pH-responsive slow-release early strength agent. The pH-responsive slow-release early strength agent of the present invention has alkali-responsive behavior, can improve the early strength of cement paste, and has no negative impact on thickening performance, thus solving the shortcomings of the current early strength agent for deepwater cementing.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a pH-responsive sustained-release early-strength agent, comprising the following steps:
[0007] The porous silicate mineral is subjected to pore expansion treatment to obtain the pore-expanded silicate mineral;
[0008] The pore-expanded silicate mineral is added to an inorganic salt solution for vacuum pumping - vacuum releasing operation to obtain the loaded silicate mineral;
[0009] The loaded silicate mineral is added to a cationic polyelectrolyte solution for film coating to obtain silicate mineral A;
[0010] The silicate mineral A is added to an anionic polyelectrolyte solution for film coating, and the steps of film coating in the cationic polyelectrolyte solution and film coating in the anionic polyelectrolyte solution are repeated to obtain the pH-responsive slow-release early strength agent.
[0011] The second technical solution of the present invention is a pH-responsive slow-release early strength agent prepared according to the above preparation method.
[0012] The third technical solution of the present invention is the application of the above pH-responsive slow-release early strength agent in cement.
[0013] The present invention discloses the following technical effects:
[0014] The present invention uses the porous silicate mineral as the adsorption carrier of the early strength agent, and utilizes its rich hollow structure to adsorb the water-soluble early strength agent. Its high surface structure and unique chemical composition can promote the development of the compressive strength of cement and avoid the development of the early strength of cement caused by the slow-release behavior.
[0015] The loaded porous silicate mineral is wrapped with polyelectrolytes with opposite charges, which can ensure that the early strength agent is not released in advance during the slurry mixing process. In the alkaline environment of cement hydration, the polyelectrolytes gradually dissociate and peel off, and the early strength agent slowly dissolves in the cement slurry. By changing the coating layer number of the polyelectrolyte, the release rate of the early strength agent is further regulated, so as to achieve release on demand and avoid the problem of rapid thickening of the cement slurry caused by the one-time addition of the inorganic salt early strength agent. Description of the Drawings
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0017] Figure 1 It is the response behavior of the pH-responsive slow-release early strength agents prepared in Example 3, Example 4 and Example 5 in an alkaline solution.
[0018] Figure 2 The thickening performance of the oil well cement stone incorporated with the pH-responsive slow-release early strength agent prepared in Example 5 at 40 °C and 20 MPa.
[0019] Figure 3 The compressive strength of the oil well cement stone incorporated with the pH-responsive slow-release early strength agent prepared in Example 5 at 1 day, 2 days and 3 days. Detailed implementation manners
[0020] The various exemplary implementation manners of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, characteristics and implementation schemes of the present invention.
[0021] It should be understood that the terms described in the present invention are only for describing specific implementation manners and are not used to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0022] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.
[0023] Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific implementation manners of the specification of the present invention, which are obvious to those skilled in the art. Other implementation manners obtained from the specification of the present invention are obvious to those skilled in the art. The specification and examples of the present invention are only exemplary.
[0024] Regarding the terms "comprising", "including", "having", "containing", etc. used herein, they are all open-ended terms, meaning including but not limited to.
[0025] Sustained-release technology combines an active substance with a sustained-release substrate, enabling the active substance to be slowly released into the external environment at a certain rate over a desired period through means such as the rupture, degradation, and penetration of the sustained-release substrate, maintaining a certain effective concentration in a certain system and prolonging the action time of the active substance. Layer-by-layer self-assembly technology is a supramolecular self-assembly technology based on the interaction between the positive and negative charges carried by polyelectrolyte anions and cations. The basic principle of this technology is that two substances with opposite charges alternately deposit on a substrate to form a multi-layer film through electrostatic force, hydrogen bonds, chemical bonds, and other interactions. The pH-responsive sustained-release technology prepared based on layer-by-layer self-assembly technology utilizes the dissociation of the polyelectrolyte film in an acidic or alkaline environment, thereby losing the protection of the active substance and achieving the purpose of sustained release.
[0026] Halloysite is a silicate mineral. Due to its hollow tubular structure with a high aspect ratio, it is commonly used as a nanocarrier for active substances to achieve the loading of various active substances and is an excellent carrier. The present invention intends to prepare a pH-responsive sustained-release early strength agent that can improve the early compressive strength of cement stone while having no negative impact on the thickening performance. The water-soluble early strength agent is loaded onto halloysite, and the surface of halloysite is coated with a film using layer-by-layer self-assembly technology. In the alkaline environment of the cement slurry, the polyelectrolyte dissociates, and the early strength agent is gradually released into the cement slurry, playing an early strength role and avoiding the rapid thickening of the cement slurry caused by the one-time addition of the early strength agent.
[0027] The first aspect of the present invention provides a preparation method for a pH-responsive sustained-release early strength agent, comprising the following steps:
[0028] Step 1, perform pore-expanding treatment on a porous silicate mineral to obtain a pore-expanded silicate mineral;
[0029] Step 2, add the pore-expanded silicate mineral to an inorganic salt solution and perform vacuum-pumping and vacuum-releasing operations to obtain a loaded silicate mineral;
[0030] Step 3, add the loaded silicate mineral to a cationic polyelectrolyte solution for film coating to obtain silicate mineral A;
[0031] Step 4, add silicate mineral A to an anionic polyelectrolyte solution for film coating, and repeat the steps of film coating in the cationic polyelectrolyte solution and film coating in the anionic polyelectrolyte solution to obtain the pH-responsive sustained-release early strength agent.
[0032] In some embodiments of the present invention, the porous silicate mineral is halloysite; the pore-expanding treatment specifically involves adding the porous silicate mineral to an acid solution and stirring; the temperature of the pore-expanding treatment is 60 - 80 °C, and the time is 4 - 6 h; before the pore-expanding treatment, there is also a step of ultrasonic dispersion to make it uniform; after the pore-expanding treatment, there are also steps of centrifugally separating the solid matter, washing, drying, and grinding. The acid solution is a strong acid solution, such as a 2 - 4 mol / L hydrochloric acid solution.
[0033] The requirement for the pore-expanding treatment is that the dosage of the strong acid can fully submerge the porous silicate mineral. If the concentration of the strong acid is too high, it is easy to cause the porous silicate mineral to be completely corroded and damaged, which is not conducive to the adsorption of inorganic salts. A suitable concentration can make the pore diameter larger without forming damage.
[0034] In some embodiments of the present invention, the inorganic salt solution is a sodium sulfate or sodium chloride solution with a concentration of 0.1 - 0.3 g / mL; the mass ratio of the pore-expanded silicate mineral to the inorganic salt solution is 1:14 - 16.
[0035] In the present invention, the reason for choosing the above range of the concentration of the inorganic salt solution is based on the solubility of the inorganic salt in water at normal temperature and negative pressure. (For example, the solubility of sodium sulfate in water at 20 °C is 19.5 g / 100 ml of water)
[0036] In the present invention, the inorganic salt solution is prepared by adding an inorganic salt (sodium sulfate or sodium chloride) to water.
[0037] In some embodiments of the present invention, the vacuum-pumping - vacuum-releasing operation specifically involves first performing a vacuum-pumping treatment for 20 - 40 min, then communicating the system with the atmosphere and maintaining it under atmospheric pressure for 5 - 10 min; the vacuum-pumping - vacuum-releasing operation is repeated 2 - 4 times. After the vacuum-pumping - vacuum-releasing operation, there are also steps of centrifugation, washing, drying, and grinding; before performing the vacuum-pumping - vacuum-releasing operation, there is also a step of ultrasonic treatment to make the pore-expanded silicate mineral uniformly disperse in the inorganic salt solution.
[0038] In some embodiments of the present invention, in step 3, the cationic polyelectrolyte solution is a poly(allylamine hydrochloride), poly(dimethyldiallylammonium chloride), poly(allylamine), or poly(ethyleneimine) solution with a concentration of 6 - 8 mg / mL; the mass ratio of the loaded silicate mineral to the cationic polyelectrolyte solution is 1:15 - 30; the time for film coating in the cationic polyelectrolyte solution is 8 - 10 min; stirring can be performed during the film coating process; the cationic electrolyte solution includes sodium chloride; the addition amount of sodium chloride is 0.04 - 0.05 g / mL; after the film coating in the cationic polyelectrolyte solution, there are also steps of centrifugation and washing the centrifuged solid.
[0039] In the present invention, the reasons for limiting the concentration of the cationic polyelectrolyte solution and the mass ratio of the loaded silicate mineral to the cationic polyelectrolyte solution within the above parameter ranges are as follows: The concentration or the mass ratio determines the thickness of the film loaded on the surface of the silicate mineral, which in turn affects the release rate of the inorganic salts within the silicate mineral. If the film thickness is too small, the inorganic salts are released quickly, without the effect of slow release. If the film thickness is too large, the release of the inorganic salts is too slow, and its action time will be prolonged.
[0040] In the present invention, the cationic polyelectrolyte solution is prepared by adding a cationic polyelectrolyte (poly(allylamine hydrochloride), poly(dimethyldiallylammonium chloride), poly(allylamine) or polyethyleneimine) to water.
[0041] In some embodiments of the present invention, in step 4, the anionic polyelectrolyte solution is a sodium carboxymethylcellulose, sodium polyacrylate, sodium alginate or polyphosphate solution with a concentration of 6 - 8 mg / mL; the mass ratio of the silicate mineral A to the anionic polyelectrolyte solution is 1:15 - 30; the time for film coating in the anionic polyelectrolyte solution is 8 - 10 min; stirring can be carried out during the film coating process; after the film coating in the anionic polyelectrolyte solution is completed, centrifugation is further included, and the steps of washing the centrifuged solid are carried out.
[0042] In the present invention, the reasons for limiting the concentration of the anionic polyelectrolyte solution and the mass ratio of the silicate mineral A to the anionic polyelectrolyte solution within the above parameter ranges are as follows: The concentration or the mass ratio determines the thickness of the film loaded on the surface of the silicate mineral, which in turn affects the release rate of the inorganic salts within the silicate mineral. If the film thickness is too small, the inorganic salts are released quickly, without the effect of slow release. If the film thickness is too large, the release of the inorganic salts is too slow, and its action time will be prolonged.
[0043] In the present invention, the anionic polyelectrolyte solution is prepared by adding an anionic polyelectrolyte (sodium carboxymethylcellulose, sodium polyacrylate, sodium alginate or polyphosphate) to water.
[0044] In the present invention, the reasons for selecting the above parameter range for the film coating time in steps 3 and 4 are as follows: If the film coating time is too short, it is likely to cause uneven film coating of the polyelectrolyte or too low content, affecting the subsequent release process of the inorganic salts. If the film coating time is too long, it is likely to cause the release of the inorganic salts in the polyelectrolyte solution. Selecting 8 - 10 min (more preferably 10 min) can ensure uniform film coating of the polyelectrolyte.
[0045] In some embodiments of the present invention, the steps of film coating in the cationic polyelectrolyte solution and film coating in the anionic polyelectrolyte solution are repeated 1 - 3 times.
[0046] After repeating the steps of coating in the cationic polyelectrolyte solution and coating in the anionic polyelectrolyte solution, it further includes the step of drying the obtained product; the drying temperature is 80 °C.
[0047] The second aspect of the present invention provides a pH-responsive sustained-release early strength agent prepared by the above preparation method.
[0048] The third aspect of the present invention provides an application of the above pH-responsive sustained-release early strength agent in cement.
[0049] In some embodiments of the present invention, the addition amount of the pH-responsive sustained-release early strength agent in cement is 1-3% of the mass of cement.
[0050] The raw materials used in the embodiments of the present invention can be obtained through commercial channels without special instructions.
[0051] In the embodiments of the present invention, "halloysite" all refers to "halloysite nanotubes".
[0052] The cement used in the embodiments of the present invention is Jiahua G-class oil well cement; other types of oil well cement can also be used in the present invention.
[0053] The mass unit in each embodiment of the present invention can be grams or kilograms or other mass units.
[0054] The following further illustrates the present invention with specific embodiments, and the protection scope and implementation manner of the present invention are not limited thereto.
[0055] Example 1
[0056] The preparation method of the pH-responsive sustained-release early strength agent is as follows:
[0057] (1) Add halloysite to 2 mol / L hydrochloric acid solution (the mass ratio of halloysite to hydrochloric acid solution is 1:16), ultrasonically disperse and stir at 80 °C for 5 h. After the reaction ends, centrifuge to separate the solid substance, wash with deionized water and dry, and grind to obtain the halloysite with enlarged pores.
[0058] (2) Add the above halloysite with enlarged pores to 0.2 g / mL sodium sulfate solution (the mass ratio of halloysite with enlarged pores to sodium sulfate solution is 1:16), stir evenly and then put it into an ultrasonic cell disruptor for ultrasonic treatment for 10 min to make the halloysite evenly dispersed in the solution; transfer the obtained uniformly dispersed suspension to a pear-shaped flask and perform vacuum pumping for 30 min. Then, make the system communicate with the atmosphere (release the vacuum) to keep the solution under atmospheric pressure for 5 min. The above vacuum pumping-releasing vacuum operation is repeated 4 times. Then, centrifuge, wash, dry and grind it to obtain the loaded halloysite.
[0059] (3) Add the loaded halloysite into a 6 mg / mL cationic polyethyleneimine solution and stir for 10 min (the mass ratio of the loaded halloysite to the cationic polyethyleneimine solution is 1:30). During this period, add sodium chloride to improve the film coating efficiency (the addition amount of sodium chloride is 0.045 g / mL), and then centrifuge and wash the solution to obtain silicate mineral A.
[0060] (4) Add the silicate mineral A obtained in step (3) above into a 7 mg / mL sodium carboxymethylcellulose solution and stir for 10 min (the mass ratio of the silicate mineral A to the sodium carboxymethylcellulose solution is 1:30), and then centrifuge and wash.
[0061] (5) Take steps (3) and (4) as one cycle and repeat it once; finally, place the centrifuged and washed silicate mineral in an 80 °C oven to dry, and grind to obtain a pH-responsive slow-release early strength agent.
[0062] Example 2
[0063] A preparation method of a pH-responsive slow-release early strength agent, the steps are as follows:
[0064] (1) Add halloysite into a 4 mol / L hydrochloric acid solution, ultrasonically disperse it, and stir at 80 °C for 5 h. After the reaction is completed, centrifuge to separate the solid matter, wash it with deionized water, dry it, and grind it to obtain expanded halloysite.
[0065] (2) Add the above-expanded halloysite into a 0.3 g / mL sodium sulfate solution (the mass ratio of the expanded halloysite to the sodium sulfate solution is 1:16), stir evenly, and then place it in an ultrasonic cell disruptor for ultrasonic treatment for 10 min to make the halloysite evenly dispersed in the solution; transfer the obtained evenly dispersed suspension to a pear-shaped flask and perform vacuum pumping for 30 min. Then, make the system communicate with the atmosphere and keep the solution under atmospheric pressure for 5 min. Repeat the above vacuum pumping - vacuum releasing operation 4 times. Then, centrifuge it, wash it, dry it, and grind it to obtain the loaded halloysite.
[0066] (3) Add the loaded halloysite into a 7 mg / mL cationic polydimethyldiallylammonium chloride solution and stir for 10 min (the mass ratio of the loaded halloysite to the cationic polydimethyldiallylammonium chloride solution is 1:30). During this period, add sodium chloride to improve the film coating efficiency (the addition amount of sodium chloride is 0.04 g / mL), and then centrifuge and wash the solution to obtain silicate mineral A.
[0067] (4) Add the silicate mineral A obtained in step (3) above into a 6 mg / mL sodium alginate solution and stir for 10 min (the mass ratio of the silicate mineral A to the sodium alginate solution is 1:30), and then centrifuge and wash.
[0068] (5) Take steps (3) and (4) as one cycle and repeat it once; finally, place the centrifuged and washed silicate minerals in an oven at 80 °C to dry, and grind to obtain a pH-responsive slow-release early strength agent.
[0069] Example 3
[0070] A method for preparing a pH-responsive slow-release early strength agent, the steps are as follows:
[0071] (1) Add halloysite to a 4 mol / L hydrochloric acid solution, ultrasonically disperse it, and stir at 80 °C for 5 h. After the reaction is completed, centrifuge to separate the solid matter, wash it with deionized water, dry it, and grind to obtain expanded halloysite.
[0072] (2) Add the above-mentioned expanded halloysite to a 0.3 g / mL sodium sulfate solution (the mass ratio of the expanded halloysite to the sodium sulfate solution is 1:16), stir evenly, and then place it in an ultrasonic cell crusher for ultrasonic treatment for 10 min to make the halloysite evenly dispersed in the solution; transfer the obtained uniformly dispersed suspension to a pear-shaped flask and perform a vacuum pumping treatment for 30 min. Then, connect the system to the atmosphere and keep the solution under atmospheric pressure for 5 min. The above vacuum pumping - vacuum releasing operation is repeated 4 times. Then, centrifuge, wash, dry, and grind it to obtain the loaded halloysite.
[0073] (3) Add the above-mentioned loaded halloysite to a 6 mg / mL cationic polyallylamine solution and stir for 10 min (the mass ratio of the loaded halloysite to the cationic polyallylamine solution is 1:30). During this period, add sodium chloride to improve the film coating efficiency (the addition amount of sodium chloride is 0.05 g / mL), and then centrifuge and wash the solution to obtain silicate mineral A.
[0074] (4) Add the silicate mineral A obtained in step (3) above to an 8 mg / mL sodium hexametaphosphate solution and stir for 10 min (the mass ratio of the silicate mineral A to the sodium hexametaphosphate solution is 1:30), and then centrifuge and wash.
[0075] (5) Take steps (3) and (4) as one cycle and repeat it twice; finally, place the centrifuged and washed silicate minerals in an oven at 80 °C to dry, and grind to obtain a pH-responsive slow-release early strength agent.
[0076] Example 4
[0077] A method for preparing a pH-responsive slow-release early strength agent, the steps are as follows:
[0078] (1) Add halloysite to a 4 mol / L hydrochloric acid solution, ultrasonically disperse it, and stir at 80 °C for 5 h. After the reaction is completed, centrifuge to separate the solid matter, wash it with deionized water, dry it, and grind to obtain expanded halloysite.
[0079] (2) Add the above-expanded halloysite into a 0.3 g / mL sodium sulfate solution (the mass ratio of the expanded halloysite to the sodium sulfate solution is 1:16). After stirring evenly, place it in an ultrasonic cell disruptor for ultrasonic treatment for 10 min to uniformly disperse the halloysite in the solution. Transfer the obtained uniformly dispersed suspension to a pear-shaped flask and perform vacuum pumping for 30 min. Then, connect the system to the atmosphere and keep the solution under atmospheric pressure for 5 min. Repeat the above vacuum pumping - releasing vacuum operation 4 times. Then, centrifuge, wash, dry, and grind it to obtain the loaded halloysite.
[0080] (3) Add the above-loaded halloysite into an 8 mg / mL cationic poly(allylamine hydrochloride) solution and stir for 10 min (the mass ratio of the loaded halloysite to the cationic poly(allylamine hydrochloride) solution is 1:30). During this period, add sodium chloride to improve the film coating efficiency (the addition amount of sodium chloride is 0.05 g / mL). Then, centrifuge and wash the solution to obtain silicate mineral A.
[0081] (4) Add the silicate mineral A obtained in step (3) above to a 6 mg / mL sodium polyacrylate solution at a ratio of 1:30 and stir for 10 min (the mass ratio of the silicate mineral A to the sodium polyacrylate solution is 1:30). Then, centrifuge and wash.
[0082] (5) Take steps (3) and (4) as one cycle and repeat it once. Finally, place the centrifuged and washed silicate mineral in an 80 °C oven to dry and grind to obtain the pH-responsive slow-release early strength agent.
[0083] Example 5
[0084] A preparation method of a pH-responsive slow-release early strength agent is as follows:
[0085] (1) Add halloysite into a 4 mol / L hydrochloric acid solution, ultrasonically disperse it, and stir at 80 °C for 5 h. After the reaction ends, centrifuge to separate the solid matter, wash it with deionized water, dry it, and grind it to obtain the expanded halloysite.
[0086] (2) Add the above-expanded halloysite into a 0.3 g / mL sodium sulfate solution (the mass ratio of the expanded halloysite to the sodium sulfate solution is 1:16). After stirring evenly, place it in an ultrasonic cell disruptor for ultrasonic treatment for 10 min to uniformly disperse the halloysite in the solution. Transfer the obtained uniformly dispersed suspension to a pear-shaped flask and perform vacuum pumping for 30 min. Then, connect the system to the atmosphere and keep the solution under atmospheric pressure for 5 min. Repeat the above vacuum pumping - releasing vacuum operation 4 times. Then, centrifuge, wash, dry, and grind it to obtain the loaded halloysite.
[0087] (3) The above-mentioned halloysite loaded with the payload was added to a 8 mg / mL solution of cationic poly(allylamine hydrochloride) and stirred for 10 min (the mass ratio of the loaded halloysite to the cationic poly(allylamine hydrochloride) solution was 1:30). During this period, sodium chloride was added to improve the film coating efficiency (the addition amount of sodium chloride was 0.045 g / mL). Then, the solution was centrifuged and washed to obtain silicate mineral A.
[0088] (4) The silicate mineral A obtained in the above step (3) was added to an 8 mg / mL solution of sodium polyacrylate at a ratio of 1:30 and stirred for 10 min (the mass ratio of the silicate mineral A to the sodium polyacrylate solution was 1:30). Then, it was centrifuged and washed.
[0089] (5) Steps (3) and (4) were regarded as one cycle and repeated 2 times. Finally, the centrifuged and washed silicate mineral was placed in an oven at 80 °C to dry, and then ground to obtain a pH-responsive slow-release early strength agent.
[0090] To detect whether the encapsulation process of the loaded halloysite was successful, a nano particle size and Zeta potential analyzer was used to test the change in surface potential during the layer-by-layer self-assembly process of the pH-responsive slow-release early strength agents (hereinafter referred to as early strength agents) prepared in Example 1, Example 2, Example 3, Example 4, and Example 5. The outer surface of halloysite is silica, which has abundant hydroxyl groups and is negatively charged in an aqueous solution with pH = 2 - 8. Therefore, the surface charge of the halloysite loaded with the early strength agent is -18.9 mV. Cationic polyelectrolytes have a high degree of ionization and are positively charged in an aqueous solution, while cationic polyelectrolytes show a negative charge in an aqueous solution. Using the principle of electrostatic attraction between positive and negative charges, cationic polyelectrolytes with positive charges can be adsorbed on the outer surface of the negatively charged halloysite. The adsorption of a large amount of cationic electrolytes causes the surface potential of the halloysite to reverse, and the Zeta potential changes from negative to positive, proving that the first layer of film coating is successful. By placing the halloysite after film coating in an anionic polyelectrolyte solution, under the action of electrostatic force, the negatively charged anionic polyelectrolyte is adsorbed on the positively charged polyelectrolyte film, resulting in the surface charge of the halloysite becoming negative. This film coating process is alternately repeated to form a polyelectrolyte protective film on the surface of the halloysite. This multi-layer film structure forms a shell-like coating layer on the halloysite, providing a diffusion barrier and slowing down the release of the early strength agent inside the halloysite. The self-healing agents prepared in Example 1, Example 2, and Example 4 are coated with 4 layers of polyelectrolytes on the surface, while the self-healing agents prepared in Example 3 and Example 5 are coated with 6 layers of polyelectrolytes on the surface. As can be seen from Table 1, due to the inconsistency of the polyelectrolytes and electrolyte concentrations used in each example, the absolute value of Zate also has certain changes. However, the Zate potential values generally show an alternating change of positive and negative, proving that the film coating is successful.
[0091] Table 1 Changes in the surface Zeta potential of the pH-responsive slow-release early strength agent prepared in Examples 1-5 during the film coating process
[0092]
[0093] Figure 1 The release behavior of sodium sulfate in deionized water and sodium hydroxide solution with pH = 13 for the pH-responsive slow-release early strength agents (hereinafter simply referred to as early strength agents) prepared in Example 3, Example 4 and Example 5. The ion concentration in the solution was detected by ion chromatography. It can be seen from Figure 1 that no obvious release of sodium sulfate occurred in the distilled water for all the early strength agents after film coating, which confirmed that the polyelectrolyte film deposited on the early strength agent could effectively coat the surface of halloysite and block the tube ends of halloysite, and successfully encapsulate sodium sulfate inside halloysite. In the sodium hydroxide solution with pH = 13, the early strength agent with 4-layer polyelectrolyte film prepared in Example 4 ( Figure 1 (b) therein) showed a slow-release behavior. After adding the NaOH solution for 2 h, due to the swelling of the encapsulated polyelectrolyte film in the alkaline environment, a small amount of sodium sulfate encapsulated between the polyelectrolyte film layers was released. With the extension of the soaking time, the release amount of sodium sulfate increased suddenly at 5 h, and the release amount increased significantly within 12 h. After 12 h, the release rate of sodium sulfate became slower, and the overall release amount increased steadily, and basically reached the equilibrium state at 168 h. Comparing its stable encapsulation in distilled water, the large amount of release of the early strength agent in the NaOH solution confirmed that the prepared slow-release early strength agent had good pH-responsive ability. The stretching and curling state and charge density of the polyelectrolyte segments were affected by the pH of the system. In a strong alkaline environment (pH>9), the groups in the polyelectrolyte backbone were deprotonated, and the charge density of the polymer segments changed. In the initial stage of deprotonation, some voids and swelling would appear in the polyelectrolyte film layer, resulting in a small amount of leakage of the content. With the extension of time, the groups were completely deprotonated, and the electrostatic interaction force between the polyelectrolytes was significantly weakened, resulting in further swelling and peeling of the polyelectrolyte film, and the halloysite loaded with sodium sulfate was completely exposed to the environment, resulting in an increase in the release rate. The slow-release early strength agents prepared in Example 3 ( Figure 1 (a) therein) and Example 5 ( Figure 1 (c) therein) had 6-layer polyelectrolyte films, so their release rates were slower than that of the early strength agent prepared in Example 4. Example 1 and Example 2 had similar release laws to Example 4, which will not be elaborated here.
[0094] The pH-responsive slow-release early strength agent prepared in Example 5 was added to the cement system at 1% of the mass of Jiahua G-class oil well cement. The preparation method of the cement slurry and the testing method of the thickening time refer to the standard GB / T.19139-2012 "Test Methods for Oil Well Cement". Figure 2It is the thickening time curve of the pH-responsive slow-release early-strength agent cement slurry prepared in Example 5. For the pure cement slurry without adding any admixtures ( Figure 2 (a) in it), the thickening time at low temperature is 409 min. The thickening time of the cement slurry added with 1% sodium sulfate continues to drop to 278 min ( Figure 2 (b) in it), indicating that the addition of sodium sulfate causes the cement slurry to thicken in a short time and the pumpability becomes worse. However, the thickening time of the cement slurry added with 1% pH-responsive slow-release early-strength agent is 316 min ( Figure 2 (c) in it), which is shorter than that of the pure cement and longer than that of the cement slurry with 1% sodium sulfate added. It is proved that sodium sulfate in the pH-responsive slow-release early-strength agent prepared in Example 5 is indeed released into the cement slurry solution. However, due to the existence of the polyelectrolyte protective film, the dissolution rate of sodium sulfate in the cement slurry solution becomes slower, and the concentration of sodium sulfate in the cement slurry decreases. Therefore, the thickening time is prolonged.
[0095] The pH-responsive slow-release early-strength agent prepared in Example 5 was added to the cement system at 1% of the mass of Jiahua G-class oil well cement. The preparation method of the cement slurry, the preparation method of the compressive strength sample and the test method refer to the standard GB / T.19139-2012 "Test Methods for Oil Well Cement". Figure 3 It is the compressive strength data of the cement slurry added with the pH-responsive slow-release early-strength agent prepared in Example 5. It can be seen from the figure that the incorporation of sodium sulfate, halloysite and pH-responsive slow-release early-strength agent all increases the early compressive strength of the cement. The compressive strength of the pure cement at 1 d is almost 0. The compressive strengths of the cement stone containing 1% sodium sulfate after curing for 1, 2, and 3 days are 9.3 MPa, 23.9 MPa, and 29.0 MPa respectively, indicating that sodium sulfate can effectively improve the early compressive strength of the cement stone. The compressive strengths of the cement stone containing 1% halloysite after curing for 1, 2, and 3 days are 8.6 MPa, 23.2 MPa, and 25.9 MPa respectively, which are much higher than the compressive strength of the pure cement. The increase in compressive strength is because halloysite can play a filling role in the cement, making the structure of the cement stone more dense. Secondly, the silica on the surface of halloysite will undergo pozzolanic reaction with the cement components to generate denser hydration products. Therefore, the early compressive strength of the cement stone can be improved. The compressive strengths of the cement stone containing 1% pH-responsive slow-release early-strength agent after curing for 1, 2, and 3 days are 9.4 MPa, 24.5 MPa, and 31.6 MPa respectively, which are higher than the strengths of the cement stones added with halloysite and sodium sulfate. This is because, in an alkaline environment, a part of the sodium sulfate in the halloysite is gradually released into the cement slurry, playing the role of early strength. Secondly, when the polyelectrolyte membrane completely falls off and the halloysite is exposed in the cement slurry, it undergoes pozzolanic reaction with the cement, thus improving the early compressive strength of the cement stone.
[0096] The pH-responsive slow-release early strength agent of the present invention has an alkali-responsive behavior, which can effectively slow down the influence of the early strength agent on the thickening time of cement, ensure the pumpability of cement, improve the early compressive strength of the cement stone, and ensure the safety of well cementing. The pH-responsive slow-release early strength agent uses halloysite as a porous carrier, and adsorbs the early strength agent through vacuum. The polyelectrolyte film is deposited on the surface of halloysite by layer-by-layer self-assembly technology for encapsulation. In the alkaline environment of the cement slurry, the polyelectrolyte film gradually dissociates and falls off, and the early strength agent is slowly released into the cement slurry, avoiding the phenomenon of rapid thickening of the cement slurry caused by one-time dosing. Secondly, the silica on the surface of halloysite can react with the cement components through pozzolanic action, which is beneficial to improving the early compressive strength of the cement stone. The pH-responsive slow-release early strength agent has the characteristics of simple preparation process, wide source of raw materials, easy to be applied in practical engineering, adjusting the thickening performance of cement slurry, and improving the compressive strength of cement stone.
[0097] The embodiments described above are only used to describe the preferred mode of the present invention, and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations and improvements made by those of ordinary skill in the art to the technical solution of the present invention shall fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a pH-responsive sustained-release early-strength agent, characterized in that: Adding a pH-responsive slow-release early-strength agent accounting for 1-3% of the cement mass to the cement; The preparation method of the pH-responsive slow-release early-strength agent comprises the following steps: Performing pore expansion treatment on porous silicate minerals to obtain pore-expanded silicate minerals; Adding the expanded silicate mineral into an inorganic salt solution and performing vacuuming-releasing operations to obtain a loaded silicate mineral; adding the loaded silicate mineral into a cationic polyelectrolyte solution for coating to obtain a silicate mineral A; The silicate mineral A is added to an anionic polyelectrolyte solution for coating, and the steps of coating in a cationic polyelectrolyte solution and coating in an anionic polyelectrolyte solution are repeated to obtain the pH-responsive slow-release early strength agent; The porous silicate mineral is halloysite; the pore expansion treatment is specifically adding the porous silicate mineral into an acid solution and stirring; the temperature of the pore expansion treatment is 60-80° C. and the time is 4-6 h; the acid solution is a hydrochloric acid solution with a concentration of 2-4 mol / L; The inorganic salt solution is a sodium sulfate or sodium chloride solution with a concentration of 0.1-0.3 g / mL; the mass ratio of the expanded silicate mineral to the inorganic salt solution is 1:14-16; The vacuuming-de-vacuuming operation specifically comprises first vacuuming for 20-40 minutes, then connecting the system to the atmosphere and maintaining it under atmospheric pressure for 5-10 minutes; the vacuuming-de-vacuuming operation is repeated 2-4 times; The cationic polyelectrolyte solution is a solution of poly(propyleneamine hydrochloride), polydimethyldiallylammonium chloride, polyallylamine or polyethyleneimine with a concentration of 6-8 mg / mL; the mass ratio of the loaded silicate mineral to the cationic polyelectrolyte solution is 1:15-30; the coating time in the cationic polyelectrolyte solution is 8-10 min; the cationic polyelectrolyte solution also includes sodium chloride; The anionic polyelectrolyte solution is a solution of sodium carboxymethyl cellulose, sodium polyacrylate, sodium alginate or polyphosphate with a concentration of 6-8 mg / mL; the mass ratio of the silicate mineral A to the anionic polyelectrolyte solution is 1:15-30; the coating time in the anionic polyelectrolyte solution is 8-10 min; The steps of coating in a cationic polyelectrolyte solution and coating in an anionic polyelectrolyte solution were repeated 1 to 3 times.
Citation Information
Patent Citations
Microcapsule for retarding oil gas well working fluid additive release and preparation method thereof
CN101144011A
Alkali response self-healing agent as well as preparation method and application thereof
CN116425445A